Outcomes and Adverse Effects of Isotretinoin in Acne Treatment: A Systematic Review - Tylczyńska, Kinga; Tylczyńska, Natalia; Skiba, Jakub; Skiba, Zuzanna; Kowalik, Kinga; Michalska, Maria; Zielińska, Aleksandra; Szypulski, Szymon; Iwaniuk, Sebastian; Maciejewski, Ignacy (Quality in Sport, 2024)
Introduction and purpose: Isotretinoin (13-cis-Retinoic Acid), is a drug for moderate to severe acne that doesn’t respond to other treatments. The purpose of this review was to present the mechanism of action, outcomes and adverse effects of isotretinoin. Description of state of knowledge: Isotretinoin is a very lipophilic drug and is used in dermatology to treat acne vulgaris due to its inhibitory effect on sebaceous gland activity and proliferation. Isotretinoin can cause side effects across various body systems. Extra caution is advised for patients with lipid abnormalities or impaired liver function. For women of reproductive age, it’s crucial to use contraception starting one month before, throughout, and for one month after isotretinoin treatment due to teratogenicity. Conclusions: Oral isotretinoin is a highly effective acne treatment that helps prevent both physical scarring and psychological impacts associated with severe acne. Although generally associated with mild and reversible side effects, isotretinoin is teratogenic, which requires careful patient management.